2018
DOI: 10.1111/tbj.13146
|View full text |Cite
|
Sign up to set email alerts
|

Robotic nipple-sparing mastectomy: The first experience from Indian subcontinent

Abstract: Breast cancer is the second most common cancer in the world and it is the leading cancer affecting Indian women. With growing numbers and increasing cosmetic concerns, more and more women are opting for breast conservation surgeries (BCS). However, in patients in whom breast conservation is not possible, skin-sparing (SSM) or nipple-sparing mastectomy (NSM) with reconstruction is the option.Endoscopic approaches came into vogue to combat the cosmetic concerns associated with open NSM but they failed to gain po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Consequently, NSM is the procedure of choice when this technique is possible, mainly in relation to the tumor nipple-areolar-complex (NACx) distance on radiologic exams. Several studies reported a few cases of robotic-NSM (R-NSM) to evaluate feasibility, reproducibility, and safety (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, a technical robotic surgical consensual NSM procedure was reported (28).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, NSM is the procedure of choice when this technique is possible, mainly in relation to the tumor nipple-areolar-complex (NACx) distance on radiologic exams. Several studies reported a few cases of robotic-NSM (R-NSM) to evaluate feasibility, reproducibility, and safety (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, a technical robotic surgical consensual NSM procedure was reported (28).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, few additional publications have described the use of RNSM ( Table 3 ) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Reported complications include nipple areolar complex necrosis, mastectomy flap necrosis, temporary skin blistering, hematoma, seroma, infection, loss of implant from infection, delayed axillary wound healing, transient brachial plexus neurapraxia (due to arm positioning), transient common peronal nerve neurapraxia (due to patient positioning during surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Total mammary glandular excision in NSM can be technically challenging, due to small size of the incision and poor visualization of the dissection plane. To help overcome the challenges in open NSM, use of the robot (da Vinci Surgical System, Intuitive Surgical, Sunnyvale, CA) for robot-assisted nipple sparing mastectomy (RNSM) is an emerging operation [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast reconstruction is then performed as with open NSM with either a tissue expander, breast implant, and/or autologous tissue flap, which is detailed in a later chapter. 20 39 42 43 45 46 47 48…”
Section: Robotic-assisted Nipple Sparing Mastectomymentioning
confidence: 99%
“…20,[42][43][44] R-NSM has been completed utilizing the da Vinci S, Si, and Xi systems (Intuitive Surgical, Sunnyvale, CA). 20,39,42,43,[45][46][47][48] The patient is placed in the supine position with the ipsilateral arm either resting below the plane of the operating table or abducted to 90 degrees on a surgical armrest attached to the operating table. Reported techniques describe the placement of 1 to 3 incisions (3-6 cm in length depending on breast size), with the main port site placed at the lateral aspect of the breast near the anterior axillary line.…”
Section: Robotic-assisted Nipple Sparing Mastectomymentioning
confidence: 99%